CAR, OER dan Inflasi sebagai Prediktor Profitabilitas - Ni Luh Putu Sri Purnama Pradnyani (Universitas Katolik Soegijapranata, Semarang, 2020)
This research wanted to determine the effect of CAR, OER, and inflation on profitability. The sample in this study was State-Owned Commercial Banks (BUMN) listed on the Indonesia Stock Exchange (BEI) in 2015-2018. The sampling method used was purposive sampling with a sample of 4 banking sector companies that met the criteria in the study. The multiple linear regression was used as data analysis technique. Based on the research results, the t value was 2.877 with sig 0.014, which means that the CAR variable has a positive and significant effect on profitability. The results of OER research show the t value of -2.684 with sig 0.020, which means that OER has a negative and significant effect on profitability. The results of the inflation study show the t value of 2.334 with sig 0.037, which means that inflation has a positive and significant effect on profitability.